Perspective And Support Of Religious Leaders In The Acceleration Of The Decline Of Stunting In East Nusa Tenggara Province - Picauly, Intje; Nur, Marselinus Laga; Oematan, Grouse; Ridwan, Nadia; Jegili, Yohanes Dwi Putra; Nenabu, Michelle Revival; Aipipidely, Diana (Universitas Muhammadiyah Tangerang, 2025)
This study aims to determine the role of religious leaders in supporting the acceleration of stunting reduction in East Nusa Tenggara. The study was conducted using a qualitative descriptive approach with informants: 10 religious leaders who were determined by Purposive Sampling using one of the inclusion criteria, namely from religious groups with the largest number of people in Indonesia and NTT Province, namely Islam, Protestantism, and Catholicism and 10 mothers of stunted toddlers and are receiving intervention programs from the Kupang Regency government. Data were collected by means of in-depth interviews, then comments or statements from informants were recorded by the prepared tool. Furthermore, the data were analyzed in four stages, namely data collection, data reduction, data presentation, and drawing conclusions. The results of the study showed that in general the perspective of religious leaders was very good that stunting was a problem of chronic malnutrition that had an impact on the quality of human resources. The form of support from religious leaders was to involve the government in efforts to change the pattern of nutrition and public health through nutrition advocacy activities, public health nutrition governance, and ensuring the involvement of the religious sector in health. Conclusion: religious leaders can be partners with the government in accelerating stunting reduction in NTT Province. Penelitian ini bertujuan untuk mengetahui peran tokoh agama dalam mendukung percepatan penurunan stunting di Nusa Tenggara Timur. Penelitian dilakukan dengan pendekatan deskriptif kualitatif bersama informan : 10 orang tokoh agama yang ditentukan secara Purposive Sampling menggunakan salah satu kriteria inkusi yaitu berasal dari kelompok agama dengan jumlah jiwa terbanyak di Indonesia dan Propinsi NTT yaitu islam, protestan, dan katholik dan 10 orang ibu balita stunting dan sedang mendapat program intervensi dari pemerintah Kabupaten Kupang. Data dikumpulkan dengan cara wawancara mendalam atau Indepth interview, kemudian komentar atau pernyataan dari informan direkam oleh alat yang disiapkan. Selanjutnya data dianalisis dengan empat tahap, yaitu pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa secara umum prespektif tokoh agama sangat baik bahwa stunting merupakan masalah kekurangan gizi kronik yang berdampak pada kualitas sumberdaya manusia. Bentuk dukungan tokoh agama adalah melibatkan pemerintah dalam upaya perubahan pola asuh gizi dan kesehatan masyarakat melalui kegiatan advokasi gizi, tata kelola gizi kesehatan masyarakat, dan menjamin keterlibatan sektor agama dalam kesehatan. Kesimpulan : tokoh agama dapat menjadi mitra pemerintah dalam percepatan penurunan stunting di Propinsi NTT.